Design and fabrication of 1.55μm broad area slotted single-mode Fabry–Perot lasers - 李梦珂 袁丽君 于红艳 阚强 李士颜 米俊萍 潘教青 (Journal of semiconductors, 2016)
We present a single-mode laser on a p-In P substrate suitable for bonding on silicon-on-insulator（SOI）wafer. The laser can realize single mode lasing with etching perturbing slots by standard photolithography and an inductively coupled-plasma（ICP） etching technique without any regrowth steps. The parameters were designed using the simulation tool ＂cavity modeling framework＂（CAMFR）. The single mode of 1539 nm wavelength at the threshold current of 130 mA with the maximum output power of 3.9 mW was obtained at 10℃ in continuouswave operation. The simple technology, low cost and the single-mode characteristics make the broad area slotted single-mode FP laser a promising light source on the silicon-based optical interconnection applications.